Occupational Health Risk Analysis and Assessment in Cement Production Processes - Karahan, Vedat; Akosman, Cevdet (Fırat University, 2018)
The purpose of this study is to determine safety risk scores by carrying out risk analysis within plant site according to the occupational health and safety risk management in the cement production processes. To determine occupational and safety risks scores, the plant site studies have been performed by using 5x5 L type risk matrix methodology in the Elazığ-Altınova Cement Plant. The plant site visit covers the sections of raw material processing, storage and transportation, raw material milling, clinker production and cement milling.  All possible risks were listed, likelihood and severity of the risks were determined and by using these values and risk scores were calculated. After determining the risks for the workers, the safety risk tables were prepared, and the possible risks were classified as high, moderate and low-risk degrees concerning occupational and safety risk management system. The results of risk assessment revealed that the most dangerous risks were came out in the raw material milling. On the other hand, the highest risk scores were also observed in the raw material milling section. It was found that the crusher, raw material and cement mills and rotary kiln are the most dust, noise, and vibration producing units.